Interferon Action on Parental Semliki Forest Virus Ribonucleic Acid - Friedman, Robert M. (1967)
Actinomycin D-treated chick fibroblasts were infected with purified (32)P-labeled Semliki forest virus, and ribonucleic acid (RNA) was extracted after 1 or 2 hr. Within 1 hr, viral RNA forms sedimenting in sucrose gradients at 42S, 30S, and 16S were present. The 42S form corresponded to the RNA of the virion. The 16S form appeared to be a double-stranded template for the formation of new viral RNA, since nascent RNA was associated with it and the molecule could be heat-denatured and subsequently reannealed by slow cooling. Interferon treatment before infection, or puromycin (50 μg/ml) or cycloheximide (200 μg/ml) added at the time of virus infection, had no effect on the formation of the 30S RNA but inhibited the production of the 16S form. Several findings made it unlikely that these results were due to breakdown of parental RNA and reincorporation of (32)P into progeny structures. The results suggested that the mechanism of interferon action involves inhibition of protein synthesis by parental viral RNA, since a specific viral RNA polymerase had previously been demonstrated to be necessary for production of 16S RNA. No protein synthesis appears necessary for formation of 30S RNA from parental virus RNA.